Digital Communication in Building Emotional Closeness in Long Distance Marriages from the Perspective of the Quran - Prakoso, Abimanyu Satrio; Noor, Marzuki; Fitriyanti; Sudarman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
Long Distance Marriage (LDM) is an increasingly common phenomenon in this era of globalization, where married couples are separated by long physical distances due to work, education, or other obligations. One of the biggest challenges that LDM couples face is maintaining emotional closeness and effective communication. This research aims to explore digital communication strategies that can be used to build and sustain emotional intimacy between husband and wife in LDM. Through qualitative methods, including in-depth interviews with 5 LDM couples, several key strategies were identified, such as the use of voice and video calls, text and voice messages, media sharing, and regular communication scheduling. The findings suggest that the quality of communication, including emotional depth, openness, and honesty, is critical in strengthening emotional bonds. Additionally, the consistency and frequency of communication are essential to keeping the relationship alive and dynamic. The Quran emphasizes the importance of communication based on truthfulness and sincerity, as seen in the verse: â€œO you who have believed, fear Allah and speak words of appropriate justiceâ€ (QS. Al-Ahzab: 70). This reinforces the idea that openness and honesty are fundamental to maintaining trust and emotional closeness, especially in LDM. The implications of this research highlight that by utilizing appropriate digital communication strategies and upholding the principles of openness and honesty, LDM couples can foster strong and enduring relationships, even when separated by physical distance.